KEBIJAKAN FORMULASI MENGENAI PERAMPASAN ASET HASIL TINDAK PIDANA KORUPSI - M Dani Fariz Amrullah D (Tazir, 2022)
orruption is an urgent problem that must be addressed immediately in order to achieve healthy economic growth. Various records show an increase and development of corruption models that occur. The theft of assets resulting from criminal acts of corruption is a development problem on the largest scale in existence. The difficulty that occurs in tracking the proceeds of a criminal act is that the assets found cannot be directly linked to the crime. The mechanism for confiscation of assets resulting from criminal acts of corruption is currently based on Article 18 letter (a) of Law Number 31 of 1999 which was later updated through the provisions of Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption (UU TIPIKOR). Meanwhile, in the context of efforts to recover assets, it can be done through a civil lawsuit mechanism, which is regulated in Articles 32 to 38 of Law Number 31 of 1999 which was updated through Law Number 20 of 2001 concerning Eradication of Corruption Crimes. the formulation regarding confiscation of assets resulting from criminal acts of corruption is guided by and refers to the civil forfeiture system used in the United Nations Convention Against Corruption (the United Nations Convention against Corruption) in returning assets resulting from criminal acts of corruption by providing an obligation to reverse the burden of proof to the suspect (defendant). . In order for the means of civil lawsuits to become a very effective tool in order to recover state losses Corruption is an urgent problem that must be addressed immediately in order to achieve healthy economic growth. Various records show an increase and development of corruption models that occur. The theft of assets resulting from criminal acts of corruption is a development problem on the largest scale in existence. The difficulty that occurs in tracking the proceeds of a criminal act is that the assets found cannot be directly linked to the crime. The mechanism for confiscation of assets resulting from criminal acts of corruption is currently based on Article 18 letter (a) of Law Number 31 of 1999 which was later updated through the provisions of Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption (UU TIPIKOR). Meanwhile, in the context of efforts to recover assets, it can be done through a civil lawsuit mechanism, which is regulated in Articles 32 to 38 of Law Number 31 of 1999 which was updated through Law Number 20 of 2001 concerning Eradication of Corruption Crimes. the formulation regarding confiscation of assets resulting from criminal acts of corruption is guided by and refers to the civil forfeiture system used in the United Nations Convention Against Corruption (the United Nations Convention against Corruption) in returning assets resulting from criminal acts of corruption by providing an obligation to reverse the burden of proof to the suspect (defendant). . So that the means of civil lawsuits becomes a very effective tool in order to restore state losses